Acetylsalicylic Acid Use in Patients with Acute Myocardial Infarction and Peptic Ulcer Bleeding. (2009) - Cheung, Justin; Rajala, Jennifer; Moroz, Daniel; Zhu, Qiaohao; Stamm, Michael; Sandha, Gurpal Singh
Abstract : BACKGROUND: Acetylsalicylic acid (ASA) is used in the treatment of acute myocardial infarction (AMI) but is also a risk factor for peptic ulcer disease (PUD) bleeding. OBJECTIVE: To determine the factors associated with continued ASA use in patients with AMI who develop PUD bleeding. METHODS: AMI patients who developed PUD bleeding during the same hospitalization at two tertiary care hospitals in Edmonton, Alberta, between January 1999 and December 2006, were evaluated retrospectively. Multivariate analysis was used to determine predictors of the primary outcome of continued ASA use during PUD bleeding. RESULTS: A total of 102 patients were analyzed. Thirty-eight patients (37%) were continued on ASA, while 64 (63%) had ASA discontinued during their hospitalization. On multivariate regression analysis, significant predictors of continued ASA use included low-risk ulcer stigmata on endoscopy (OR 3.7; 95% CI 1.4 to 10.2; P=0.01) and AMI requiring coronary intervention (OR 8.2; 95% CI 2.1 to 32.1; P=0.002). The mean (± SD) blood transfusion requirement was 3.9±3.6 units. The 30-day rebleeding and mortality rates were 14% and 14%, respectively. CONCLUSIONS: The continued use of ASA during AMI and PUD bleeding was variable. However, patients with low-risk ulcers and those who received coronary intervention were more likely to have ASA continued during PUD bleeding. Further studies evaluating the gastrointestinal risk of immediate ASA use in AMI with acute PUD bleeding are required.